2008
DOI: 10.1080/14756360801936274
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activities of sesquiterpene lactone from Carpesium cernum

Abstract: The whole plant of genus Carpesium is used in traditional medicine as an anti-pyretic, analgesic and vermifugic, including a topical application for sores and inflammation. Previous experiments on Carpesium rosulatum suggested that the antiplasmodial effect was due to the existence of ineupatorolide A. In present paper, screening of Carpesium species from South Korea showed that this plant refers to which species had promising antiplasmodial activity. Subsequently, this species was selected for bioassay-guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…(Euphorbiaceae) and displayed antiplasmodial activity (IC 50 values of 8.7 and 9.9 µM, respectively) against K1 [25]. Fractionation of the ethyl acetate extract of Carpesium cernuum L. (Asteraceae) yielded four characterised sesquiterpenoid lactones among which 11(13)-dehydroivaxillin (57) and 11-epi-ivaxillin (58) exhibited antiplasmodial activity against D10 with IC 50 values of 2.0 and 9.3 µM [34]. In vivo antiplasmodial activity of 57 showed a suppression of parasitemia of 58.6 % with a dose of 2 mg/kg/day in the four-day test [35].…”
mentioning
confidence: 99%
“…(Euphorbiaceae) and displayed antiplasmodial activity (IC 50 values of 8.7 and 9.9 µM, respectively) against K1 [25]. Fractionation of the ethyl acetate extract of Carpesium cernuum L. (Asteraceae) yielded four characterised sesquiterpenoid lactones among which 11(13)-dehydroivaxillin (57) and 11-epi-ivaxillin (58) exhibited antiplasmodial activity against D10 with IC 50 values of 2.0 and 9.3 µM [34]. In vivo antiplasmodial activity of 57 showed a suppression of parasitemia of 58.6 % with a dose of 2 mg/kg/day in the four-day test [35].…”
mentioning
confidence: 99%
“…Sesquiterpenoid lactones are a series of well-known compounds that have been reported to have various bioactivities, including antiplasmodial, antiproliferative, and antifungal activities. Several bioactive germacranolide-type sesquiterpenoid lactones have been isolated recently, most often from the Asteraceae family. , Previous structure–activity relationship studies indicated that the α,β-unsaturated γ-lactone unit, which could target cysteine residues in proteins by acting as a Michael acceptor, is important for the bioactivity of germacranolides . This α,β-unsaturated γ-lactone unit is present in all four trichospirolides A–D, but their activities are varied due to modifications in the 10-membered ring.…”
Section: Resultsmentioning
confidence: 99%
“…In the tribe Vernonieae (family: Asteraceae) sesquiterpene lactones (Lopes, 1991) are found, for which the different biological effects are described. The data suggest that these compounds have anti-inflammatory and anti-ulcer (Feltenstein et al, 2004), anti-malarial (Chung & Moon, 2009), and antibacterial (Ntutelaa et al, 2009, Saroglou et al, 2010 properties. These results could be related to the α,β-unsaturated carbonyl groups in these compounds, which seems to be important for their cytotoxicity (Lee et al, 1971).…”
Section: Discussionmentioning
confidence: 99%